PENGARUH HUBUNGAN KERJA, KOMUNIKASI, DAN TINGKAT KESEJAHTERAAN TERHADAP KINERJA KARYAWAN PADA PERUSAHAAN PT. BPR SARI DANANIAGA TABANAN - Novayana, Edy; Sudarma, Nyoman (E-Jurnal Manajemen; Vol 3 No 5 (2014), 2014)
The purpose of this study is (1) want to know the influence of the working relationship of employee performance at PT BPR Sari Dananiaga Tabanan, (2) determine the effect of communication on employee performance at PT BPR Sari Dananiaga Tabanan, (3) determine the effect of the welfare of the employee's performance PT BPR Sari Dananiaga Tabanan. The research was conducted at the Industrial PT BPR Sari Dananiaga  Tabanan with data analysis techniques multiple linear regression. Number of samples obtained by using census method is of 61 respondents. Based on the results of the analysis it can be concluded that the employment relationship has a positive and significant influence on the performance of the Industrial PT BPR Sari Dananiaga Tabanan. Communication has a positive and significant influence on the performance of the Industrial PT BPR Sari Dananiaga Tabanan. Level of welfare has a positive and significant influence on employee performance in the Industrial PT BPR Sari Dananiaga Tabanan. This is evident from the calculated t value is greater than the t table. Communication is the most influential variable on employee performance Industrial PT BPR Sari Dananiaga Tabanan. Keywords: Performance, work relations, communications and social well being.
Keywords: Kinerja; hubungan kerja; komunikasi dan tingkat kesejahteraan